Ordered membrane electrode and preparation method thereof

By constructing a carbon support array structure on the cathode side of the composite membrane of the membrane electrode and loading Pt particles, the transmission restriction caused by the random distribution of the existing membrane electrode catalytic layer is solved, higher performance and stability are achieved, and Pt is reduced Use amount.

CN119447337APending Publication Date: 2025-02-14SHANGHAI ANCHI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411462921.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The catalytic layers of existing membrane electrodes are randomly distributed, resulting in limited transport of protons, electrons and substances, limiting the performance and life of fuel cells.

Method used

By constructing a carbon support array structure on the cathode side of the composite membrane and uniformly loading Pt particles on its surface, an ordered proton, electron and substance transport channel is formed.

Benefits of technology

It achieves better mass transfer performance under high current density, improves the performance and stability of the membrane electrode, and reduces Pt load and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447337A_ABST
    Figure CN119447337A_ABST
Patent Text Reader

Abstract

The present invention relates to an ordered membrane electrode and a method for preparing the same, the ordered membrane electrode comprising a composite membrane having an anode side and a cathode side, a cathode catalyst loading layer loaded on the cathode side, and an anode catalyst loading layer loaded on the anode side, the cathode side having a carbon carrier array structure, the loading amount of Pt in the cathode catalyst loading layer being controlled to 0.15-0.25 mg / cm < 2 >, and the loading amount of Pt in the anode catalyst loading layer being controlled to 0.15-0.25 mg / cm < 2 >. The loading amount of Pt in the anode catalyst loading layer is controlled to be 0.06-0.1 mg / cm < 2 >; the preparation method of the ordered membrane electrode comprises the following steps: S1, dispersing the carbon carrier; s2, preparing a mixed filling liquid; s3, preparing a composite membrane; s4, preparing a carbon carrier array structure on one side of the composite film; s5, loading a cathode catalyst; and S6, loading an anode catalyst. The mass transfer loss is effectively reduced, and the battery performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to an ordered membrane electrode and a preparation method thereof. Background Art

[0002] With the development of social economy, the demand for clean energy is becoming more and more urgent. Proton exchange membrane fuel cell (PEMFC) has attracted widespread attention due to its advantages such as environmental friendliness, high conversion efficiency and the ability to operate at low temperatures, and has gradually been commercialized on a large scale. However, the high cost and low life of PEMFC hinder its further commercial development. Membrane-electrode assembly (MEA) is the core component that determines the performance and stability of PEMFC. Therefore, material optimization and structural design of membrane electrode assemblies such as proton exchange membrane (PEM), catalyst layer (CL), and gas diffusion layer (GDL) are considered to be important means to effectively improve the performance and life of fuel cells.

[0003] At present, membrane electrodes are mainly prepared by catalyst-coated membrane (CCM), that is, the catalyst slurry is loaded onto the surface of the proton exchange membrane by spraying or direct coating to form a three-in-one membrane electrode. However, the catalytic layer of the membrane electrode prepared by this method is randomly distributed, the internal pores and catalyst particles are in a disordered state, and the proton transport, electron transport and material transport are limited, resulting in limited performance of the membrane electrode at high current density. Studies have shown that constructing specific ordered structures within the membrane electrode can further improve the performance and life of the membrane electrode. These ordered structures can provide ordered proton, electron or material transmission channels, thereby reducing the transmission resistance and improving the catalyst performance while reducing the platinum loading. Summary of the invention

[0004] In order to solve the above problems in the prior art, the present invention provides an ordered membrane electrode and a preparation method thereof which can reduce mass transfer loss to improve battery performance.

[0005] To achieve the above object, according to one aspect of the present invention, there is provided an ordered membrane electrode, comprising: A composite membrane comprising an anode side and a cathode side, the cathode side having a carbon support array structure; A cathode catalyst support layer, which is supported on the cathode side of the composite membrane, wherein the Pt loading in the cathode catalyst support layer is controlled to be 0.15 to 0.25 mg / cm2; The anode catalyst supporting layer is supported on the anode side of the composite membrane, and the Pt loading in the anode catalyst supporting layer is controlled to be 0.06 to 0.1 mg / cm2.

[0006] According to another aspect of the present invention, there is provided a method for preparing an ordered membrane electrode, comprising the following steps: S1: dispersion of carbon carrier: adding carbon carrier to dispersant, crushing carbon carrier into smaller size by ultrasonic crusher, and then filtering and drying; S2: Preparation of mixed filling liquid: The dried carbon support was mixed with 5.00 wt.% perfluorosulfonic acid solution and ultrasonically dispersed, and then diluted with anhydrous ethanol to prepare a mixed filling liquid; S3: Preparation of composite membrane: a certain volume of mixed filling liquid is measured to fill the porous alumina template with it, and then placed in a vacuum device for vacuum treatment to discharge the air in the microporous structure of the porous alumina template (i.e., AAO template) so that the mixed filling liquid can be completely filled into the microstructure of the porous alumina template; S4: The porous alumina template is then placed on a heating table to completely evaporate the solvent, and then a commercial proton exchange membrane is placed on the surface thereof, and heating is continued to allow the two to be tightly bonded. After cooling, the porous alumina template is immersed in water, and the membrane is completely peeled off to obtain a composite membrane with a carbon carrier array structure on one side; S5: Cathode catalyst loading: The side of the composite membrane with the carbon carrier array structure is used as the cathode side, a high-purity platinum target is used as the sputtering source, argon gas is introduced as the sputtering atmosphere, and the Pt particles are uniformly loaded onto the surface of the carbon carrier array structure by magnetron sputtering, and the Pt loading amount is controlled to be 0.15-0.25 mg / cm2; S6: Anode catalyst loading: One side of the composite membrane's carbon-free carrier array structure is the anode side, and a commercial Pt / C catalyst is used for loading. The catalyst, 5.00wt.% perfluorosulfonic acid solution, isopropanol, and water are mixed in a certain mass ratio to obtain a catalyst slurry, which is then subjected to high shear dispersion. Finally, the catalyst slurry is loaded on the membrane surface through a coating device, and the Pt loading amount is controlled to be 0.06-0.1mg / cm2 to obtain a complete ordered membrane electrode.

[0007] Furthermore, in step S1, the carbon carrier includes but is not limited to carbon nanotubes, carbon nanowires, carbon nanorods, activated carbon, carbon black, graphene or carbon microspheres; the dispersant is one or more of ethanol, ethylene glycol, isopropanol, glycerol, and chloroform; the concentration of the carbon carrier in the dispersant is 1 to 2 mg / ml, the ultrasonic power is 50 to 100 W, the ultrasonic time is 10 to 20 h, the drying temperature is 80 to 120 ° C, and the baking time is 1 to 6 h.

[0008] Furthermore, in step S2, the perfluorosulfonic acid solution is Nafion from DuPont, the mass ratio of the ionic polymer (ionomer, i.e., the solid component in the solution, represented by I) in Nafion to the carbon carrier (carbon, represented by C) (i.e., I / C ratio) is 0.5-1.5:1, and the stirring time is 0.5-2h.

[0009] Furthermore, in step S2, the dilution ratio of the anhydrous ethanol is 5 to 20 times, and the stirring time is 20 to 40 minutes.

[0010] Furthermore, in step S3, the microporous structure of the porous alumina template is a V-shaped channel or a columnar channel, the channel height is 1 to 3 um, and the center distance between adjacent channels is 100 to 500 nm.

[0011] Furthermore, in the step S3, the mixed filling liquid is used to cover the porous alumina template at a ratio of 1 to 2 ml per 25 square centimeters of the porous alumina template, and the vacuuming time is 20 to 40 minutes.

[0012] Furthermore, in step S4, the temperature of the heating stage is 120-150° C., and the heating time for evaporating the solvent is 30-60 minutes, and the heating time for continuing to heat the composite membrane to bond is 10-30 minutes.

[0013] Furthermore, in the step S5, during the cathode side magnetron sputtering, the vacuum degree of the chamber is lower than 2×10-4 Pa, the pressure in the chamber is 0.5-0.7 Pa, and the current is 50-200 mA.

[0014] Furthermore, in step S6, the mass ratio of the catalyst, 5.00wt.% perfluorosulfonic acid solution, isopropanol, and water is 1:5-15:10-15:15-25, the high shear dispersion time is 30-50min, and the coating process is spraying, wherein the perfluorosulfonic acid solution is Nafion from DuPont of the United States.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1) The carbon support array structure constructed on the cathode side of the composite membrane of the membrane electrode of the present invention can provide more active sites for the catalyst, and can provide smooth and complete proton, electron and material transmission channels while reducing the Pt loading, and has better mass transfer performance under high current density, thereby improving the performance of the membrane electrode under high current density; 2) The carbon support array structure in the present invention is prepared by an AAO template, and the morphology and size are highly controllable and consistent, so that the membrane electrode has better consistency and stability; 3) The steps involved in the present invention are simple and easy to implement. The process steps adopted, such as ultrasonic crushing, hot pressing, magnetron sputtering and spraying, are all relatively mature technologies with wide applications. The prepared membrane electrode has good performance and is suitable for large-scale batch production.

[0016] These and other aspects of the invention will be more clearly elucidated with reference to the embodiments described hereinafter. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Further advantages of the present invention will be better understood through the following description in conjunction with the accompanying drawings: Figure 1 3 are polarization curves of membrane electrodes obtained according to Examples 1-3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings. Example 1

[0019] S1: Using carbon nanotubes as carbon carriers, using isopropanol / glycerol with a volume ratio of 1:1 as a dispersion solvent, adding carbon nanotubes into the dispersion solvent composed of isopropanol / glycerol, controlling the concentration of carbon nanotubes to be 1 mg / ml, adjusting the ultrasonic power to 50 W, and the ultrasonic time to 10 h. After the ultrasonic treatment, filtering it, and then drying it in an oven at 80 ° C for 1 h to obtain carbon nanotube powder; S2: adding the carbon nanotube powder in step S1 to a Nafion solution with a mass fraction of 5.00wt.% (from DuPont, USA), controlling the I / C ratio to 0.5:1, and then stirring for 0.5h to disperse it, and then diluting it 5 times with anhydrous ethanol, stirring for 20min to disperse it evenly, to obtain a mixed filling liquid; S3: The AAO template channels are cylindrical channels with a channel height of 1um and a hole center distance of 100nm. A 25cm2 AAO template is cut out, 1ml of the mixed filling liquid in step S2 is measured to evenly cover the AAO template, and then the template is placed in a vacuum device for evacuation for 20 minutes; S4: After the vacuum treatment is completed, the template is placed on a 120°C heating table and heated for 30 minutes. Then, a commercial proton exchange membrane (8um fuel cell proton exchange membrane from GORE, USA) is placed on the template surface and heated for 10 minutes to allow the two to be tightly combined. After cooling, the template is immersed in water and the membrane is completely peeled off to obtain a composite membrane with a carbon carrier array structure on one side. S5: The side of the composite film with the carbon carrier array structure is used as the cathode side, and a high-purity platinum target is used as a sputtering source. Pt particles are loaded by magnetron sputtering. The vacuum degree of the cavity is controlled at 1×10-4Pa. After the vacuum degree meets the requirements, argon gas is introduced as the sputtering atmosphere, and the pressure in the cavity is controlled to be 0.5Pa, the current is 50mA, and the Pt loading is controlled to be 0.15mg / cm2; S6: The unstructured side of the composite membrane is the anode side, which is loaded with a commercial Pt / C catalyst (TEC10E50E produced by Tanaka Precious Metals (TKK) of Japan, with a platinum mass fraction of 47%). The catalyst, 5.00wt.% Nafiton solution, isopropanol, and water are mixed in a mass ratio of 1:5:10:15, and then high shear dispersion is performed for 30 minutes. Finally, the catalyst slurry is evenly loaded on the membrane surface through a spraying process, and the Pt loading is controlled to 0.06mg / cm2 to obtain a complete CCM. Example 2

[0020] S1: Using carbon nanotubes as carbon carriers, using isopropanol / glycerol with a volume ratio of 1:1 as a dispersion solvent, adding carbon nanotubes into the dispersion solvent composed of isopropanol / glycerol, controlling the concentration of carbon nanotubes to be 1.5 mg / ml, adjusting the ultrasonic power to 80 W, and the ultrasonic time to 15 h. After the ultrasonic treatment, filtering it, and then drying it in an oven at 100 ° C for 3 h to obtain carbon nanotube powder; S2: adding the carbon nanotube powder in step S1 to a Nafion solution with a mass fraction of 5.00wt.% (from DuPont, USA), controlling the I / C ratio to be 1:1, and then stirring for 1h to disperse it, and then diluting it 12 times with anhydrous ethanol, stirring for 30min to disperse it evenly, to obtain a mixed filling liquid; S3: The AAO template channels are cylindrical channels with a channel height of 2um and a hole center distance of 300nm. A 25cm2 AAO template is cut out, 1.5ml of the mixed filling liquid in step S2 is measured to evenly cover the AAO template, and then the template is placed in a vacuum device for 30 minutes; S4: After the vacuum treatment is completed, the template is placed on a 130°C heating table and heated for 45 minutes. Then, a commercial proton exchange membrane (8um fuel cell proton exchange membrane from GORE, USA) is placed on the template surface and heated for another 20 minutes to allow the two to be tightly combined. After cooling, the template is immersed in water and the membrane is completely peeled off to obtain a composite membrane with a carbon carrier array structure on one side. S5: The side of the composite film with the carbon carrier array structure is used as the cathode side, and a high-purity platinum target is used as a sputtering source. Pt particles are loaded by magnetron sputtering. The vacuum degree of the cavity is controlled at 1×10-4Pa. After the vacuum degree meets the requirements, argon gas is introduced as the sputtering atmosphere, and the pressure in the cavity is controlled to be 0.6Pa, the current is 100mA, and the Pt loading is controlled to be 0.2mg / cm2; S6: The unstructured side of the composite membrane is the anode side, which is loaded with a commercial Pt / C catalyst (TEC10E50E produced by Tanaka Precious Metals (TKK) of Japan, with a platinum mass fraction of 47%). The catalyst, 5.00wt.% Nafiton solution, isopropanol, and water are mixed in a mass ratio of 1:10:12:20, and then high shear dispersion is performed for 40 minutes. Finally, the catalyst slurry is evenly loaded on the membrane surface by a spraying process, and the Pt loading is controlled to 0.08mg / cm2 to obtain a complete CCM. Example 3

[0021] S1: Using carbon nanotubes as carbon carriers, using isopropanol / glycerol with a volume ratio of 1:1 as a dispersion solvent, adding carbon nanotubes into the dispersion solvent composed of isopropanol / glycerol, controlling the concentration of carbon nanotubes to be 2 mg / ml, adjusting the ultrasonic power to 100 W, and the ultrasonic time to 20 h. After the ultrasonication is completed, filtering it, and then placing it in a 120°C oven to dry for 6 h to obtain carbon nanotube powder; S2: adding the carbon nanotube powder in step S1 to a Nafion solution with a mass fraction of 5.00wt.% (from DuPont, USA), controlling the I / C ratio to 1.5:1, and then stirring for 2h to disperse it, and then diluting it 20 times with anhydrous ethanol, stirring for 40min to disperse it evenly, to obtain a mixed filling liquid; S3: The AAO template channels are cylindrical channels with a channel height of 3um and a hole center distance of 500nm. A 25cm2 AAO template is cut out, 2ml of the mixed filling liquid in step S2 is measured to evenly cover the AAO template, and then the template is placed in a vacuum device for 40 minutes; S4: After the vacuum treatment is completed, the template is placed on a 130°C heating table and heated for 45 minutes. Then, a commercial proton exchange membrane (8um fuel cell proton exchange membrane from GORE, USA) is placed on the template surface and heated for another 30 minutes to allow the two to be tightly combined. After cooling, the template is immersed in water and the membrane is completely peeled off to obtain a composite membrane with a carbon carrier array structure on one side. S5: The side of the composite film with the carbon carrier array structure is used as the cathode side, and a high-purity platinum target is used as a sputtering source. Pt particles are loaded by magnetron sputtering. The vacuum degree of the cavity is controlled at 1×10-4Pa. After the vacuum degree meets the requirements, argon gas is introduced as the sputtering atmosphere, and the pressure in the cavity is controlled to be 0.7Pa, the current is 200mA, and the Pt loading is controlled to be 0.25mg / cm2; S6: The unstructured side of the composite membrane is the anode side, which is loaded with a commercial Pt / C catalyst (TEC10E50E produced by Tanaka Precious Metals (TKK) of Japan, with a platinum mass fraction of 47%). The catalyst, 5.00wt.% Nafiton solution, isopropanol, and water are mixed in a mass ratio of 1:15:15:25, and then high shear dispersion is performed for 50 minutes. Finally, the catalyst slurry is evenly loaded on the membrane surface by a spraying process, and the Pt loading is controlled to 0.1mg / cm2 to obtain a complete CCM. Comparative Example 1

[0022] 1) A commercial Pt / C catalyst (TEC10E50E produced by Tanaka Precious Metals (TKK) of Japan, with a platinum mass fraction of 47%) was used for loading. The catalyst, 5.00wt.% Nafiton solution, isopropanol, and water were mixed in a mass ratio of 1:10:12:20, and then high shear dispersion was performed for 40 minutes; 2) The catalyst slurry in step S1 is evenly loaded on the surfaces of both sides of the proton exchange membrane (using the 8um fuel cell proton exchange membrane of GORE, USA) through a spraying process, and the loading amount of Pt on the anode is controlled to be 0.1 mg / cm2 and the loading amount of Pt on the cathode is controlled to be 0.3 mg / cm2 to obtain a complete CCM.

[0023] It should be noted that the performance characterization of the membrane electrode was carried out on a commercial fuel cell test bench. The CCM in the above embodiment was cut into a size of 5x5cm, assembled into a single cell with a gas diffusion layer, and polarization tested on a fuel cell test bench. The cell temperature was controlled to 80°C, the anode and cathode back pressures were 170kPa and 150kPa respectively, the hydrogen and air stoichiometric ratios were 1.5 and 1.8 respectively, and the anode and cathode humidity were 50%RH respectively. The performance of the membrane electrode was evaluated under this condition.

[0024] like Figure 1As shown, the performance of the membrane electrodes prepared by Examples 1 to 3 of the present invention is higher than that of Comparative Example 1, and is more obvious under high current density. This is mainly because the ordered design of the carbon carrier on the cathode side provides more pathways for electron transfer, proton transfer and material transfer, effectively reducing mass transfer losses, thereby improving battery performance.

[0025] In addition, if Figure 1 As shown, even in the present invention, the battery performance of the three embodiments is high and low. The performance of Embodiment 1 and Embodiment 3 is lower than that of Embodiment 2. This is because too low or too high Pt loading will lead to performance degradation. Too low Pt loading will lead to insufficient reaction active sites, while too high Pt loading will also result in agglomeration and reduce activity.

[0026] The technical content and technical features of the present invention have been disclosed above, but it is understood that under the creative ideas of the present invention, those skilled in the art can make various changes and improvements to the above structure, including the combination of technical features disclosed or claimed separately here, and other combinations that obviously include these features. These variations and / or combinations all fall within the technical field involved in the present invention and fall within the protection scope of the claims of the present invention.

Claims

1. An ordered membrane electrode, characterized in that include: A composite membrane comprising an anode side and a cathode side, the cathode side having a carbon support array structure; The cathode catalyst support layer is supported on the cathode side of the composite membrane, and the Pt loading in the cathode catalyst support layer is controlled to be 0.15-0.25 mg / cm 2 ; The anode catalyst support layer is supported on the anode side of the composite membrane, and the Pt loading in the anode catalyst support layer is controlled to be 0.06-0.1 mg / cm 2 .

2. A method for preparing an ordered membrane electrode, characterized in that The steps include: S1: dispersion of carbon carrier: adding carbon carrier to dispersant, crushing carbon carrier into smaller size by ultrasonic crusher, and then filtering and drying; S2: Preparation of mixed filling liquid: The dried carbon support was mixed with 5.00 wt.% perfluorosulfonic acid solution and ultrasonically dispersed, and then diluted with anhydrous ethanol to prepare a mixed filling liquid; S3: Preparation of composite membrane: a certain volume of mixed filling liquid is measured to fill the porous alumina template with it, and then placed in a vacuum device for vacuum treatment to discharge the air in the microporous structure of the porous alumina template so that the mixed filling liquid can be completely filled into the microstructure of the porous alumina template; S4: The porous alumina template is then placed on a heating table to completely evaporate the solvent, and then a commercial proton exchange membrane is placed on the surface thereof, and heating is continued to allow the two to be tightly bonded. After cooling, the porous alumina template is immersed in water, and the membrane is completely peeled off to obtain a composite membrane with a carbon carrier array structure on one side; S5: Cathode catalyst loading: The side of the composite membrane with the carbon carrier array structure is used as the cathode side, a high-purity platinum target is used as the sputtering source, argon gas is introduced as the sputtering atmosphere, and the Pt particles are uniformly loaded onto the surface of the carbon carrier array structure by magnetron sputtering. The Pt loading is controlled to be 0.15-0.25 mg / cm 2 ; S6: Anode catalyst loading: One side of the composite membrane without carbon support array structure is the anode side, and commercial Pt / C catalyst is used for loading. The catalyst, 5.00wt.% perfluorosulfonic acid solution, isopropanol, and water are mixed in a certain mass ratio to obtain a catalyst slurry, which is then dispersed by high shear. Finally, the catalyst slurry is loaded on the membrane surface by a coating device, and the Pt loading is controlled to be 0.06-0.1mg / cm 2 , and a complete ordered membrane electrode is obtained.

3. The method for preparing an ordered membrane electrode according to claim 2, characterized in that: In step S1, the carbon carrier includes but is not limited to carbon nanotubes, carbon nanowires, carbon nanorods, activated carbon, carbon black, graphene or carbon microspheres; the dispersant is one or more of ethanol, ethylene glycol, isopropanol, glycerol, and chloroform; the concentration of the carbon carrier in the dispersant is 1 to 2 mg / ml, the ultrasonic power is 50 to 100 W, the ultrasonic time is 10 to 20 h, the drying temperature is 80 to 120 ° C, and the baking time is 1 to 6 h.

4. The method for preparing an ordered membrane electrode according to claim 2, characterized in that: In the step S2, the perfluorosulfonic acid solution is Nafion from DuPont, USA, the mass ratio of the ionic polymer in Nafion to the carbon carrier is 0.5-1.5:1, and the stirring time is 0.5-2h.

5. The method for preparing an ordered membrane electrode according to claim 4, characterized in that: In the step S2, the dilution ratio of the anhydrous ethanol is 5 to 20 times, and the stirring time is 20 to 40 minutes.

6. The method for preparing an ordered membrane electrode according to claim 2, characterized in that: In the step S3, the microporous structure of the porous alumina template is a V-shaped channel or a columnar channel, the channel height is 1 to 3 um, and the center distance between adjacent channels is 100 to 500 nm.

7. The method for preparing an ordered membrane electrode according to claim 6, characterized in that: In the step S3, the mixed filling liquid is used to cover the porous alumina template at a ratio of 1 to 2 ml per 25 square centimeters of the porous alumina template, and the vacuuming time is 20 to 40 minutes.

8. The method for preparing an ordered membrane electrode according to claim 2, characterized in that: In step S4, the temperature of the heating stage is 120-150° C., and the heating time for evaporating the solvent is 0.5-1 hour, and the heating time for continuing to heat the composite membrane to bond is 10-30 minutes.

9. The method for preparing an ordered membrane electrode according to claim 2, characterized in that: In the step S5, the vacuum degree of the chamber during the cathode side magnetron sputtering is less than 2×10 -4 Pa, the pressure in the cavity is 0.5~0.7Pa, and the current is 50~200mA.

10. The method for preparing an ordered membrane electrode according to claim 2, characterized in that: In step S6, the mass ratio of the catalyst, 5.00wt.% perfluorosulfonic acid solution, isopropanol and water is 1:5-15:10-15:15-25, the high shear dispersion time is 30-50min, and the coating process is spraying, wherein the perfluorosulfonic acid solution is Nafion from DuPont of the United States.